Analysis of broken records in swimming at the Olympic Games held in Rio in 2016 - Durovic, M.; Okicic, T.; Madic, D.; Thanopoulos, V.; Kabanov, A.; Pesic, M. (FIS communications in Physical Education, Sport and Recreation, 2016)
Summer Olympics Games in Rio 2016 were the XXXI modern Olympic Games. These sporting events took place at 37 venues in Rio de Janeiro. Swimming has been in the Olympic Games since Athens 1896. Men and women participate in 16 events, including relays and individual competitions in four strokes. The aim of our study is to analyze in details broken records by athletes, nations and continents in recently completed Olympic Games, Rio 2016. The number of broken records on this Olympic Games is: eight World (3 man and 5 woman), 23 Olympic records (7 man and 16 woman), three Africa records (1 man and 2 woman), nine USA records (3 man and 6 woman), three Asia records (3 man), seven Europe records (3 man and 4 woman) and one Oceania record (1 women). The most broken records are performed by women (20 man, 34 woman) from which we can conclude that a woman swimming in the world is in great expansion.